EP671 Genital warts in pregnancy-diagnosis and treatement the most common cause of laryngeal paillomatosis in children under 10 years old. (1st November 2019) - Jeremic, I
Abstract : Introduction/Background: HPV infection is an epidemic of modern age with the highest number of infected girls between 18 and 30 years of age. Due to the alerted immune status during pregnancy the spreading of HPV infection is progressive. During the labor any retention of the child in the birth canal leads to aspiration of HPV particles witch further represents the most common cause of laryngeal papillomatosis in children. Methodology: The study involved 60 pregnant women between 18 and 30 years of age diagnosed with genital warts in early and advanced stages that were treated with RF technique which enables the smooth vaginal delivery with no signs of HPV infection on genito-anal region. Radio wave technique involves a special combination of radio wave access evaporisation and radio wave melting. Radio wave access evaporisation causes the evaporation of HPV infected cells and by radio wave melting we get the bloodless removal of condyloma. Results: With Colposcopic examination we reveal subclinical stages of genital warts on the mucous membrane of the labia and the entrance to the vagina, which provides conditions for their immediate removal. The result of radio wave therapy is a bloodless surgical field with a precise and controlled removal of all forms of genital warts in one act throughout pregnancy. Operation is performed only under local anesthesia with a minimum damage to the surrounding healthy tissue, rapid recovery without accompanying infection, bleeding, recurrence, and a complete protection to the mother and fetus. Conclusion: Genital warts during pregnancy represent a risk to the fetus during vaginal childbirth regardless of the severity of the clinical picture. Absence of colposcopic diagnosis, avoiding removing warts in the pregnancy, use of the wrong treatment leads to progress of condylomata as for outputting an infection of the fetus, by aspiration of HPV particles in the birth canal. Disclosure: Nothing to disclose.